ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY (UPLC) METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF ETOPHYLLINE AND THEOPHYLLINE IN PHARMACEUTICAL DOSAGE FORM: Pharmaceutical Science-Analytical Chemistry - N. WADIA, DEVANG.; T. DESAI, HEMANT. (International Journal of Life Science and Pharma Research, 2012)
A simple, precise, accurate and validated reverse phase UPLC method has been developed for the simultaneous estimation of Etophylline and Theophylline in injectables. The quantification was carried out using Silica gel column, packed with octadecylsilane , 2.1 mm × 100 mm, i.d, 1.7 µm particle size and separation was carried out in an isocratic mode, having a mixture of 0.05 M Sodium Acetate and Acetonitrile (90:10), pH 4.5 and mobile phase at a flow rate of 0.3 ml / min. The detection wavelength was 270 nm at ambient temperature. The retention time was 2.368 min and 3.129 min for Theophylline and Etophylline respectively. The results obtained showed a good agreement with the declared content. Recovery values for Theophylline and Etophylline were 99.84 - 100.89 %. The proposed method is reliable, rapid, precise, selective and may be used for the quantitative analysis of Theophylline and Etophylline in injectables.